Perlindungan Hukum Terhadap Data Pengguna Whatsapp Berdasarkan Undang-Undang Nomor 19 Tahun 2016 - Sintya, Yuli (Universitas Medan Area, 2024)
Today, the very rapid development of the world has influenced very advanced digitization. As social media users, we need an account to use social media. When creating an account, users must submit personal information on their mobile phone in the form of search history, location, and phone numbers. Privacy is a right that everyone has, given the accelerating pace of science and technology, which is the driving force behind the efficiency of technology users to continue to communicate, obtain information, and do anything related to the Internet. People feel safe using social media, especially WhatsApp when there is a principle of consumer protection. In consumer protection, several legal principles attempt to provide a basic understanding of regulation. The rapid development of social media, one of which is the WhatsApp application, is because everyone has their own media. This means that all social media users have access to everything, even if it is slow or even without much cost